STRATEGI DAN PROSEDUR PENERJEMAHAN IDIOM BAHASA JEPANG DALAM KOMIK DORAEMON TEEMA BETSU KESSAKU SEN EDISI 1—17 - Elfayanti, Wika (Humanis, 2015)
The title of this research is “A Strategy and Procedure of Japanese Idioms Translation in Doraemon Teema Betsu Kessaku Sen Comics Edition 1—17” This research describe the translation strategies and procedures applied in translating Japanese idioms. The theories used in this research are translation strategies according to Baker (1992) and translation procedures according to Vinay and Darbelnet (in Venuti, 2000). The data were analyzed with translational equal method and technique of selective decisive element. The results of this research show that from 34 idioms, 28 idioms are translated by paraphrase, 5 idioms are translated into target language’s idioms, and 1 idiom is not translated. In addition, 2 are idioms translated with literal translation procedure, 17 idioms are translated with transposition procedure, 8 idioms are translated with adaptation procedure, and 7 idioms are translated by equivalence procedure.
Keywords: idiom translation, translation strategy, translation procedure